Lumbar Diastomatomyelia with Syringomyelia: A Case Report - Gyawali, Deepika; Lama, Dharana; Pradhananga, Amit B; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2019)
Diastomatomyelia (DM) is a clinical condition in which the spinal cord is split into two portions by either a bony or a fibrous spur. Depending on the type of dural involvement, it is divided into type 1 and type 2. We recently came across a 9-month old child with a lumbar DM with syringomyelia who was managed successfully at our institute. We discuss the management of this patient in detail along with the description of its etiology, embryology, neurological manifestations, relevant investigations, and treatment implications to both patients and parents. To the best of our knowledge, this is the first case report of DM from Nepal in an infant with minimal symptoms.